PRODUKSI POLI-Î²-HIDROKSIBUTIRAT (PHB) OLEH BAKTERI AMILOLITIK DENGAN SUBSTRAT PATI SUWEG (Amorphophallus campanulatus) - , RARAS MULAT SARI, Prof. Dr. Sebastian Margino ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Poly-Î²-hidroxybutyrate (PHB) has been known as one of the raw material of bioplastic that was synthesized by bacteria. Glucose as the main carbon source for PHB production but its cost was expensive, so we need to substitute with another substrate, including starch.The ability of amylolytic bacteria hydrolyzed starch into simple sugars can be used to minimize the costs of PHB production. This research aim was to find out amylolitic bacterial isolates and produce PHB using the selected isolate. A total of 52 bacteria were isolated using starch medium from soil sample around Amorphophallus campanulatus plant. Twenty eight among of them had amylase activity, and eleven among of them had amylase activity value equal or more than 2 point.The next selection was done based on the specific amylase activity and found that five of those isolates had specific amylase activity more than 10 DUN/mg.Final selection was done based on PHB production and found that isolate E5 had the high amylase activity and PHB production. PHB production used isolate E5 in optimum conditions (inoculum concentration 10 %, elephant foot yam starch 3 %, medium pH 7, temperature 30 Â°C, agitation 125 rpm, and 48 hour incubation time)showed that percentage of PHB increased from 0,0095% to 0,145% and cell dry weight (CDW) from 1 to 6,9 gram. Characterization and identification showed that isolate E5 closed to the genus Bacillus.